'Racism under the radar': Student perceptions of school experiences in a multicultural context. Issue 5 (2nd September 2016) - Zinga, Dawn Michelle; Gordon, Megan Kathleen
Abstract : In this study focus groups were conducted to explore Aboriginal and Caucasian student perceptions of school experiences within a multicultural context. Five major themes emerged from students' dialogues that pose several questions about what sort of racist atmosphere the members of this community are being exposed to on a daily basis. The findings of this study underscore an understanding of Aboriginal student resiliency within a school setting that employs successful school initiatives that aim to promote student success. Further inquiry into these findings is needed.